The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/ijms20194808
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA Expression Pattern and ceRNA and miRNA–mRNA Networks Involved in Anther Development in the CMS Line of Brassica campestris

Abstract: Male-sterile plants provide an important breeding tool for the heterosis of hybrid crops, such as Brassicaceae. In the last decade, circular RNAs (circRNAs), as a novel class of covalently closed and single-stranded endogenous non-coding RNAs (ncRNAs), have received much attention because of their functions as “microRNA (miRNA) sponges” and “competing endogenous RNAs” (ceRNAs). However, the information about circRNAs in the regulation of male-sterility and anther development is limited. In this study, we estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 47 publications
4
31
0
Order By: Relevance
“…CircRNA studies are likely to grow in several branches of biology, both on model (Weigelt et al 2020) and non-model organisms and beyond the biomedical field (Wu et al 2021a; Chu et al 2021; Liang et al 2019), prompting the development of improved tools allowing more extensive circRNA investigation to unravel circRNA-related condition peculiarities, such as differential circRNA expression (Gaffo et al 2019; Wu et al 2021c; Tian et al 2020), imbalances of the CLP (Buratin et al 2020), and prevailing circular transcript isoform expression (Izuogu et al 2018). CirComPara2 is a resource tool meeting these needs, as already proved by the successful application of its embryonic implementations in several studies of human diseases and of other species, including plants (Gaffo et al 2019; Frydrych Capelari et al 2019; Buratin et al 2020; Dal Molin et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…CircRNA studies are likely to grow in several branches of biology, both on model (Weigelt et al 2020) and non-model organisms and beyond the biomedical field (Wu et al 2021a; Chu et al 2021; Liang et al 2019), prompting the development of improved tools allowing more extensive circRNA investigation to unravel circRNA-related condition peculiarities, such as differential circRNA expression (Gaffo et al 2019; Wu et al 2021c; Tian et al 2020), imbalances of the CLP (Buratin et al 2020), and prevailing circular transcript isoform expression (Izuogu et al 2018). CirComPara2 is a resource tool meeting these needs, as already proved by the successful application of its embryonic implementations in several studies of human diseases and of other species, including plants (Gaffo et al 2019; Frydrych Capelari et al 2019; Buratin et al 2020; Dal Molin et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the pathogenesis of OLP needs to be studied, and effective therapeutic targets for the prevention and treatment of this disease need to be found. CircRNAs can act as miRNA sponges to abolish the inhibitory effects of miRNAs on their target mRNAs, thus increasing the expression levels of mRNAs (14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…Since Hansen et al (11) first published a paper on the function of circRNA in the Nature journal in 2013, an increasing number of studies have shown that circRNAs play important roles in the pathogenesis of diseases and are potential molecular markers (12,13). By binding micro (mi) RNA through miRNA response elements, circRNAs act as "miRNA sponges" to undermine the inhibitory effects of miRNAs on their target mRNAs and thus regulate the expression level of mRNAs (14)(15)(16). The expression of circRNAs in the process of immune response and immunerelated diseases can be altered (17).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the circRNA circ_001350 regulates glioma cell proliferation, apoptosis, and metastatic properties by acting as a miRNA sponge [64]. In plants, circRNA-miRNA-mRNA networks have been identified, but they have not been confirmed by experiments [31,65]. To reveal whether DEcircRNAs can target miRNAs and participate in the transcriptional regulation of genes, we identified 385 DEcircRNAs predicted to contain miRNA decoy sites.…”
Section: Discussionmentioning
confidence: 99%